Mechanical and Thermal Properties of a Cu-CNT Composite with Carbon Nanotubes Synthesized by CVD Process - Guler, Omer (Carl Hanser Verlag, 2014)
In this study, carbon nanotubes at 0.05-1 wt-% ratios reinforced pure copper powder. Carbon nanotubes (CNT) were used to reinforce the copper matrix, these materials were synthesized under laboratory conditions. Ultrasonic processes and ball-milling method were used to provide a homogenous dispersion during production of the Cu-CNT composite. The Cu-CNT composite powder was produced as bulk material and then, the thermal conductivity as well as the microhardness of the composite were measured. As a particular result, it turned out that the thermal conductivity and the hardness of the composite increased up to a specific ratio of the CNT reinforcement, while the reinforcement ratio exceeding this critical level provided an adverse effect.
Keywords: Materials testing; Cu-CNT composite; carbon nanotubes; hardness; thermal properties